Low-Pressure Laparoscopic Surgery is a Viable and Risk-Free Alternative to Standard Pressure for the Treatment of Benign Gall Stone - Imran Ali, Gul Naz, Sauleha Sayyed, Zahid Rasheed, Muhammad Rizwan, Fawad Hameed, Muhammad Khurram Jameel, (Pakistan Journal of Medical & Health Sciences, 2023)
When compared to the open cholecystectomy, laparoscopic cholecystectomy (LC) has the benefits of less post-operative pain and quicker return to work. However, up to 80% of individuals after laparoscopic surgery still experience significant pain and needing pain relief. Methodology: The reason for this research was to compare the results of LC performed with and without LPP. LC requires the surgeon to choose a pneumoperitoneum pressure that maximizes working space while avoiding unintended side effects. This study used a Randomized Controlled Trial (RCT) design, and it was done at the West Surgical Ward at Mayo Hospital in Lahore. The study enrolled 60 participants who met the inclusion criteria. The patients were split in two groups: Low-pressure pneumoperitoneum-LPP (Group A) (06-10 mm of Hg) and pneumoperitoneum at standard pressure (SPP) is part of Group B. (12-16 mm of Hg). All had opted for a LC to treat their symptomatic gallstone disease. At 4, 8, and 24 hours following surgery, the severity of postoperative shoulder pain (if present) was evaluated using a visual analogue pain scale (VAS). The frequency of postoperative nausea and vomiting was assessed at 4, 8, 12, and 24 hours. Results: The patients were 35.63 years old on average. Majority of these two groups has no complications. Based on the data, we discovered that the frequency of episodes of nausea/vomiting in both groups was very low and that only a few patients had bouts of nausea/vomiting in the 4 hours and 24 hour time intervals. Conclusion: We have come to the conclusion that LP laparoscopic surgery is a viable and risk-free alternative to SP laparoscopic operation for the treatment of benign gall stone disorders. Our findings lead us to the conclusion that LPP is a superior option for the LC since it reduces the post-operative pain in the shoulder and the risk of PONV while not significantly increasing the risk of intraoperative complications. Keywords: Benign Gall Stone, Treatment, Low-Pressure Laparoscopic Surgery,